Complex correlations between microstructure and magnetic behavior in SrFe12O19 hexaferrite nanoparticles - Pierfrancesco Maltoni (Nature Portfolio, 2021)
Abstract The magnetic properties of SrFe12O19 (SFO) hard hexaferrites are governed by the complex relation to its microstructure, determining their relevance for permanent magnets´ applications. A set of SFO nanoparticles obtained by sol–gel self-combustion synthesis was selected for an in-depth structural X-Rays powder diffraction (XRPD) characterization by means of G(L) line-profile analysis. The obtained crystallites´ size distribution reveal a clear dependence of the size along the [001] direction on the synthesis approach, resulting in the formation of platelet-like crystallites. In addition, the size of the SFO nanoparticles was determined by transmission electron microscopy (TEM) analysis and the average number of crystallites within a particle was estimated. These results have been evaluated to illustrate the formation of single-domain state below a critical value, and the activation volume was derived from time dependent magnetization measurements, aiming to clarify the reversal magnetization process of hard magnetic materials.